Behavioral model of business change management in relation to building competitiveness in market economy conditions - Vrtana, David; Rosnerova, Zuzana; Krizanova, Anna (Business: Theory and Practice, 2021)
In the current market environment, the actual dynamics of the application of internal corporate factors is differentiated. The company thus tries to influence customers’ shopping behavior as effectively as possible. Therefore, it is important for the company to be able to adapt to these changes as effectively as possible. The purpose of the article is to analyze the factors influencing consumer behavior in the market conditions of the Slovak Republic. We described the current situation by a survey, which we conducted in 2020–2021. Among the selected categorical variables, we verified the dependence in two hypotheses by the statistical method of Pearson’s Chi-Square test. Using the method, we pointed out the factors that influence consumer behavior and can be important for change management. We compared the results of the survey with the results of similar surveys conducted abroad. Accepting the results of the survey, we proposed a general model of change management in the discussion part of the article. The model is thus a practical implication for companies with a differentiated subject of business. It also takes into account the behavioral characteristics that the company should adapt to in the current situation in order to achieve its strategic goals.